An Analysis of the Accuracy of Four Macroeconometric Models - Fair, Ray C. (Journal of Political Economy, 1979)
The primary purpose of this paper is to compare the predictive accuracy of four models: (1) Sargent's classical macroeconometric model, (2) Sim's six-equation unconstrained vector autoregression model, (3) a "naive" eighth-order autoregressive model, and (4) my model. A recent method that I have proposed for estimating the predictive accuracy of a model, which takes account of the four main sources of uncertainty of a forecast, is used for the comparisons. The results indicate that Sargent's and Sims's models are the same as or less accurate than the naive model, depending on the variable, and that my model is more accurate for real GNP, the GNP deflator, and the unemployment rate and less accurate for the money supply and the wage rate than the naive model. A secondary purpose of the paper is to point out some econometric mistakes that Sargent made in his empirical work and to propose an alternative technique that can be used to estimate a rational expectations model like his.